Pragmatic Competence in English Language Lessons - Procházková, Natálie (Univerzita Pardubice, 2023)
This master thesis focuses on the development of pragmatic competence in speaking. The aim of the theoretical part is to define the concept of pragmatics from the linguistic as well as didactic perspective. The theoretical part describes the opportunities for the development of pragmatic competence in the process of teaching and learning spoken production and interaction. The practical part contains a discussion of the findings of the action research carried out at the elementary school.
Pragmatická kompetence ve výuce anglického jazyka
Keywords: pragmatic competence; teaching speaking; elementary school; pragmatická kompetence; výuka mluveného projevu; základní škola